How do Asian candidates fare in IELTS? A look at 15 years of performance data - Pearson, William S. (Penerbit Universiti Kebangsaan Malaysia, 2021)
IELTS (International English Language Testing System) and its Asian test-takers have shared a heightening interdependency over the previous two decades. In order to achieve ambitions for an international education at Australian, Canadian, New Zealand, and UK universities, growing numbers of Asian prospective international students, particularly from China and India, find themselves required to undertake IELTS to demonstrate evidence of the sufficiency of their English language proficiency. Such is their importance to the tertiary education sectors of these countries that Asian candidates, who regularly constitute over 25 of the most common 40 cohorts of test-takers by nationality, have been key drivers of the more than ten-fold increase in the global IELTS candidature since 2003. The present study investigates how cohorts from 24 Asian nations fared in the Academic IELTS test from 2003 to 2018, utilising official performance data released by the IELTS partners. The study revealed that; 1) candidates from Hong Kong, Malaysia, and the Philippines registered the highest overall and section band scores across Asia; 2) the most sizeable overall score gains were made by Bangladeshi, Indonesian, and Jordanian candidates; and 3) worrying deteriorations in outcomes were exhibited by Emirati, Indian, and Iraqi test-takers. Implications of the findings are discussed in terms of Anglophone universities’ academic admission practices and the need for further research.